2021
DOI: 10.1186/s12199-020-00925-x
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of short-term exposure to ambient airborne pollutants on COPD-related mortality among the elderly residents of Chengdu city in Southwest China

Abstract: Background Chronic obstructive pulmonary disease (COPD) has become a severe global burden in terms of both health and the economy. Few studies, however, have thoroughly assessed the influence of air pollution on COPD-related mortality among elderly people in developing areas in the hinterland of southwestern China. This study is the first to examine the association between short-term exposure to ambient airborne pollutants and COPD-related mortality among elderly people in the central Sichuan B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Moreover, the authors observed that the association of SO 2 and NO 2 with ALRI hospitalizations became partially statistically insignificant after mutual adjustments. This observation is similar to the results of a number of previous studies [ 56 ]. There may be an interaction between SO 2 and NO 2 ; moreover, both particulate matter and NO 2 are traffic-related pollutants and are highly correlated [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the authors observed that the association of SO 2 and NO 2 with ALRI hospitalizations became partially statistically insignificant after mutual adjustments. This observation is similar to the results of a number of previous studies [ 56 ]. There may be an interaction between SO 2 and NO 2 ; moreover, both particulate matter and NO 2 are traffic-related pollutants and are highly correlated [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…The season of testing was winter, so the exposure levels of O3 in spring, summer and Autumn were included. According to the previous studies, the concentrations of O3 in the air were higher in summer and lower in spring and autumn, so no significant harmful effects of O3 on lung function in children were found in this study (Chen et al, 2021).…”
Section: Discussionsupporting
confidence: 61%
“…Sulfur dioxide (SO 2 ), mainly comes from various industrial processes, transportation, and vehicles, power plants, and fuel (coal) combustion, is one of the most common and irritant air pollutants in developing countries and industrialized areas ( 2 5 ). Several epidemiological studies have revealed that SO 2 exposure is related to human respiratory health ( 6 , 7 ), including stimulating the respiratory tract ( 8 ), leading to the decline of pulmonary function ( 9 , 10 ), and the increased mortality due to respiratory diseases ( 11 , 12 ). However, there are few studies on the relationship between SO 2 and respiratory morbidity in developing countries.…”
Section: Introductionmentioning
confidence: 99%